Sequence Read Depth Analysis of a Monophyletic Cluster of Y Chromosomes Characterized by Structural Rearrangements in the AZFc Region Resulting in DYS448 Deletion and DYF387S1 Duplication - Ravasini, Francesco; D’Atanasio, Eugenia; Bonito, Maria; Bonucci, Biancamaria; Della Rocca, Chiara; Berti, Andrea; Trombetta, Beniamino; Cruciani, Fulvio (Frontiers in Genetics, 2021)
The azoospermia factor c region (AZFc), located in the long arm of the human Y chromosome, is frequently involved in chromosome rearrangements, mainly due to non-allelic homologous recombination events that occur between the nearly identical sequences (amplicon) that comprises it. These rearrangements may have major phenotypic effects like spermatogenic failure or other pathologies linked to male infertility. Moreover, they may also be relevant in forensic genetics, since some of the Y chromosome short tandem repeats (Y-STRs) commonly used in forensic analysis are located in amplicons or in inter-amplicon sequences of the AZFc. In a previous study, we identified four phylogenetically related samples with a null allele at DYS448 and a tetrallelic pattern at DYF387S1, two Y-STRs located in the AZFc. Through NGS read depth analysis, we found that the unusual Y-STR pattern may be due to a 1.6 Mb deletion arising concurrently or after a 3.5 Mb duplication event. The observed large genomic rearrangement results in copy number reduction for the RBMY gene family as well as duplication of other AZFc genes. Based on the diversity of 16 additional Y-STRs, we estimated that the duplication/deletion event occurred at least twenty generations ago, suggesting that it has not been affected by negative selection.